Wealth concentration over the path of development: Sweden, 1873 - 2005 - Jesper Roine; Daniel Waldenström (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
We study the development of wealth concentration in Sweden over 130 years, from the begin-ning of industrialization until present day. Our series are based on a wide array of new evi-dence from estate- and wealth tax data, estimates of foreign and domestic family firm-wealth and of pension and social security wealth. We find that the Swedish wealth concentration was at a historically high level in the agrarian state and that it did not change much during early in-dustrialization. From World War I up until about 1950, the richest percentile lost ground to the rest of the top wealth decile where relatively income rich households accumulated new wealth. In the postwar period, the entire top decile lost out relative to the rest of the population, much due to the spread of owner-occupied housing. Around 1980, wealth compression stopped and inequality increased. We introduce new ways of approximating the effects of international flows and find that the recent increase in Swedish wealth inequality is likely to be larger than what official estimates suggest.
Keywords: D14; D31; N33; N34; 330; Wealth concentration; Wealth distribution; Inequality; Income distribution; Sweden; Welfare state; Pension wealth; Augmented wealth; Vermögensverteilung; Einkommensverteilung; Alterssicherung; Entwicklung; Sozialstaat; Wirtschaftsgeschichte; Schweden